Chapter 9 Religious violence in late antique Egypt reconsidered the cases of Alexandria, Panopolis, and Philae - Dijkstra, Jitse H. F. (Taylor & Francis, 2018)
Religious violence needs to be analysed on a case-by-case basis and in the context of the particular local and historical circumstances in which it arises, a theoretical premise that has also been applied to late antiquity. Stephen Emmel has conducted a meticulous analysis of all available passages on religious violence in the Shenoutian corpus. The idea that religious violence was endemic in the late antique world has remained influential. Scholars of Late Antique Studies are becoming increasingly critical of the literary accounts that describe violence between Christians and "pagans". This chapter discusses three cases that have been taken as exemplary for widespread religious violence in late antique Egypt or even for the pervasive nature of religious violence in the late antique world. The expansion of Christianity at Philae conforms entirely to similar developments in the rest of the region or, for that matter, in Egypt as a whole.